THE ROLE OF TAMAN BACA ANJELAS IN EARLY CHILDREN EDUCATION IN BIJELI VILLAGE, NOEMUTI DISTRICT, NORTH CENTRAL TIMOR, NUSA TENGGARA TIMUR - Chorilifa Safe Naibobe (JARITA : Journal of Children’s Education and Learning Research, 2023)
Early Childhood Education (PAUD) is a level of education before basic education as well as a form of education that focuses on laying the foundation for physical growth and development, namely motor coordination and intelligence which includes thinking power, creativity, emotional intelligence, spiritual intelligence. social emotional conditions (attitudes, behavior, and religion) as well as language and communication. This has a very positive impact on various aspects of early childhood. Some literature states that early childhood education is very exciting for children about the world of education with various positive activities. This article uses a qualitative method with a literature study approach related to the role of Taman Baca Ancepat. Andefini Reading Park is a learning group formed as a form of concern for education in East Nusa Tenggara, especially in Bijeli Village, Noemuti District, North Central Timor Regency.